Tamponade and massive pleural effusions secondary to peripherally inserted central catheter in neonates–A complication to be aware of - Zareef, Rana; Anka, Mariam; Hatab, Taha; El Rassi, Issam; Yunis, Khalid; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2023)
Background Peripherally inserted central catheters (PICC) are frequently used in neonatal intensive care units (NICU) to assist premature and critically ill neonates. Massive pleural effusions, pericardial effusions, and cardiac tamponade secondary to PICC are extremely uncommon but have potentially fatal consequences. Objective This study investigates the incidence of tamponade, large pleural, and pericardial effusions secondary to peripherally inserted central catheters in a neonatal intensive care unit at a tertiary care center over a 10-year period. It explores possible etiologies behind such complications and suggests preventative measures. Study design Retrospective analysis of neonates who were admitted to the NICU at the AUBMC between January 2010 and January 2020, and who required insertion of PICC. Neonates who developed tamponade, large pleural, or pericardial effusions secondary to PICC insertion were investigated. Results Four neonates developed significant life-threatening effusions. Urgent pericardiocentesis and chest tube placement were required in two and one patients, respectively. No fatalities were encountered. Conclusion The abrupt onset of hemodynamic instability without an obvious cause in any neonate with PICC in situ should raise suspicion of pleural or pericardial effusions. Timely diagnosis through bedside ultrasound, and prompt aggressive intervention are critical.